Destination Image Mediates the Influence of Experience Quality on Revisit Intention to Goa Boki Moruru - Musa, Musdalifa; Mahungo, Yolanda; Laela, Laela (AIBPM Publisher, 2024)
The purpose of this study is to investigate the direct and indirect effects of experience quality on the intention to revisit, as well as the role of the destination's image as a mediating variable. The sample for this quantitative study consists of 112 domestic travelers who have made more than two trips to Goa Boki Moruru. A questionnaire that combined purposive and incidental sampling methods was used to gather data. Smart Partial Least Square (Smart PLS) version 4.0 is the data analysis technique that is employed. The study's findings show that: (1) experience quality has no bearing on the intention to return; (2) experience quality positively affects the destination's image; (3) the destination's image positively affects the intention to return; and (4) the image of the destination completely mediates the relationship between experience quality and the intention to return